Premarital Sexual Behavior in Middle School Students: Family Conditions and Information Sources - Maria Nona Nancy; Chatarina Novianti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Premarital sexual behavior is a teenage problem that gets a lot of attention globally. This study aims to determine premarital sexual behavior in adolescents in terms of family conditions and sources of sexuality information. Family conditions can be seen from several indicators, including based on caregivers, primary caregivers, place of residence and family integrity. The researcher developed a scale based on sexual behavior, specifically touching, kissing, making out (petting), and having sex (coitus). The respondents of this study were teenagers in Sikka Regency, totaling 348 people with an age range of 12–18 years. Data analysis was performed using descriptive statistics. This study found that premarital sexual behavior in adolescents in Sikka Regency was enough high at 82%. Other findings show that the highest premarital sexual behavior in adolescents occurs in adolescents who are cared for by grandparents, while the main caregivers who are most at risk are those whose children are cared for by other families, living in boarding houses with orphaned conditions. Another condition is that teenagers who are most vulnerable to sexual behavior are teenagers who get sexual information from the media.